Analysis of heavy rainfall and barrier-jet evolution during Mei-Yu season using multiple Doppler radar retrievals: a case study on 11 June 2012. Issue 1 (1st January 2019) - Ke, Ching-Yin; Chung, Kao-Shen; Chen Wang, Tai-Chi; Liou, Yu-Chieng
Abstract: An extremely heavy precipitation event that occurred over northern Taiwan during the Mei-Yu season is analysed using radar-network observations. Radiosonde observations demonstrate the existence of a barrier jet during this event, while radar data illustrate the gradual transition from trailing stratiform precipitation to parallel stratiform precipitation as the system approached and made landfall over Taiwan. In addition, line convection parallel to the orography was initiated at the southern edge of the main precipitation before merging to form a special Y-shaped echo near the coast, and this feature repeated twice within two hours. Through multiple analyses of three different Doppler radars every 30 minutes for a period of four hours, 3-D wind fields are retrieved over the ocean and the complex terrain of Taiwan using a variational algorithm, while the pressure and temperature structure are derived from the retrieved wind fields. The migration and intensity of the barrier jets at convective scales is revealed by a vorticity budget analysis. It is found that, taken together, the stagnated Mei-Yu front, the location and the strength of the barrier jet and cold pool, as well as orographic blockage over northern Taiwan explain the formation of this quasi-stationary and extremely heavy rainfall case. A schematic model of extreme heavy rainfall over complex terrain is presented.